The Effect of Methylmercury Exposure on Astrocyte of Cerebellar Cortex of White Rats (Rattus novergicus) - Sugianto, Paulus; Pardede, Sabrina Melisa; Widjaja, Ngakan Made Rai; Widjiati, Widjiati (Folia Medica Indonesiana, 2019)
The aim of this research was to investigate the effect of different dose methylmercury (II) chloride on astrocyte in cerebellar cortex of white rat (Rattus norvegicus) exposed. This study used randomized control design using 15 adult female Wistar rats weight 180-200 g of body weight. Before treatment the white rats was adapted in a week, then randomly divided into 3 groups each consist of 5 rats. P0 as control were given 0.5 ml aquades, P1 and P2 were given 0.1 and 0.2 mg/kg/day respectively. All groups were given treatment per oral in 30 days with sonde. The data was analyzed by ANOVA, Duncan's multiple range (Duncan's Multiple Range Test). White rats exposed by methylmercury (II) chloride, had a significant differences in the percentage of necrotic astrocyte (p<0.05). Methylmercury chloride exposure increases the number of necrotic astrocytes on white rat.